Perbedaan Fonologi Bahasa Indonesia Dan Bahasa Jerman - Misela Audila Jahrani; Aura Salsabila; Alya Amelia Nurhaliza (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study aims to find out the differences contained in. German phonological system, Indonesian phonological system. This place of research is not tied to one place because the objects studied are in the form of text, namely Indonesian journals and German. This form of research is qualitative descriptive with content analysis method. The results of this study that Indonesian and German phonological differences are seen in the number of vowel and consonant phonemes. The Indonesian vocal system has five vowel phonemes. German has a relatively more diverse vowel variant than other languages, there are 15 vowels in total. The difference between Indonesian and German consonant phonemes lies in the phonemes /ɔ/ʊ/, /ɛ:/ and /ɛ/, /ø:/and also /œ/ which are not present in Indonesian. Differences in Indonesian and German phonology can make it difficult for Indonesian speakers to understand German, and vice versa.